Evaluation of phenolic compounds and antioxidant capacity in Mucuna pruriens and Cajanus cajan pods extracts - Avalos, Beatriz Itati (2023)
The seeds of Mucuna pruriens (Mp) and Cajanus cajan (Cc) legumes are known to be rich in phenolic compounds (PC) that have various beneficial properties. However, there is limited knowledge on the composition of their pods (Mp-p and Cc-p, respectively), which are considered as agricultural waste. This study investigated the extraction of PC with antioxidant capacity (AOC) from in Mp-p and Cc-p using different solvents and the decoction method. The results showed that 50 % ethanol and 100 % methanol were the most effective solvents for extracting PCs with AOC from Mp-p and Cc-p, respectively. The decoction method was also found to be efficient for extracting PCs from Mp-p. The major PC detected in Mp-p extracts were caffeic acid and chlorogenic acid, while quercetin was found in high amounts in Cc-p extracts. Moreover, the combination of Density Functional Theory and the quantum theory of atom in molecules approaches allowed to provide a detailed understanding of the relationship between the PC detected in the extracts and their antioxidant activity. The results suggest that both Mp-p and Cc-p are viable sources of natural antioxidants with potential health benefits.